Clarifying the murk: unveiling bacterial dynamics in response to crude oil pollution, Corexit-dispersant, and natural sunlight in the Gulf of Mexico - Matallana-Surget, Sabine; Nigro, Lisa M.; Waidner, Lisa A.; Lebaron, Philippe; Wattiez, Ruddy; Werner, Johannes; Fraser, Rosie; Dimitrov, Daniel; Watt, Rowan; Jeffrey, Wade H. (Frontiers in Marine Science, 2024)
The 2010 Deepwater Horizon (DwH) Oil spill released an enormous volume of oil into the Gulf of Mexico (GoM), prompting the widespread use of chemical dispersants like Corexit® EC9500A.The ecological consequences of this treatment, especially when combined with natural factors such as sunlight, remain unexplored in the context of marine bacterial communities' dynamics.To address this knowledge gap, our study employed a unique metaproteomic approach, investigating the combined effects of sunlight, crude Macondo surrogate oil, and Corexit on GoM microbiome across different mesocosms. Exposure to oil and/or Corexit caused a marked change in community composition, with a decrease in taxonomic diversity relative to controls in only 24 hours. Hydrocarbon (HC) degraders, particularly those more tolerant to Corexit and phototoxic properties of crude oil and/or Corexit, proliferated at the expense of more sensitive taxa. Solar radiation exacerbated these effects in most taxa. We demonstrated that sunlight increased the dispersant's toxicity, impacting on community structure and functioning. These functional changes were primarily directed by oxidative stress with upregulated proteins and enzymes involved in protein turnover, general stress response, DNA replication and repair, chromosome condensation, and cell division. These factors were more abundant in chemically treated conditions, especially in the presence of Corexit compared to controls. Oil treatment significantly enhanced the relative abundance of Alteromonas, an oil-degrading Gammaproteobacteria. In combined oil-Corexit treatments, the majority of identified protein functions were assigned to Alteromonas, with strongly expressed proteins involved in membrane transport, motility, carbon and amino acid metabolism and cellular defence mechanisms. Marinomonas, one of the most active genera in dark conditions, was absent from the light treatment. Numerous metabolic pathways and HC-degrading genes provided insights into bacterial community adaptation to oil spills. Key enzymes of the glyoxylate bypass, enriched in contaminant-containing treatments, were predominantly associated with Rhodobacterales and Alteromonadales. Several proteins related to outer membrane transport, photosynthesis, and nutrient metabolisms were characterized, allowing predictions of the various treatments on biogeochemical cycles. The study also presents novel perspectives for future oil spill clean-up processes.